PENGARUH MENTAL ACCOUNTING TERHADAP KEPATUHAN WAJIB PAJAK - Sadrin Sadrin; Anik Malikah; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to determine how the influence of mental accounting which consists of: 1). How is the influence of attitude, Mental Budgeting and Tax Planning on taxpayer compliance, 2). How does attitude affect taxpayer compliance, 3). How does Mental Budgeting affect taxpayer compliance, and 4). How does Tax Planning influence taxpayer compliance?Based on the results of data analysis from the study, it was found that simultaneously Attitude, Mental Budgeting and Tax Planning had a positive and significant effect with a  F value of 48.083>F table 2.629 and a significant F value of 0.000<0.05. Partially the attitude variable has a positive and significant effect on taxpayer compliance with a t value of 2.136 >t table 1.966 and a significance value of 0.033<0.05. Mental budgeting has a positive and significant effect on taxpayer compliance with a t value of 2.012>t table 1.996 and a significance value of 0.045<0.05. And Tax planning has a positive and significant effect on taxpayer compliance with a t value of 8.142>t table 1.996 and a significance value of 0.000 <0.05.Keywords : Mental Accounting, Attitude , Mental Budgeting, Tax Planning